An evaluation of the effect of infertility on marital, sexual satisfaction indices and health-related quality of life in women - Sameer Valsangkar; Trupti Bodhare; Samir Bele; Surendranath Sai (Wolters Kluwer Medknow Publications, 2011)
Background : The effect of infertility on marital and sexual functioning, health-related quality of life (QoL) and the acceptability of the treatment modalities is a poorly researched area in India. Aims and Objectives : To measure and compare the impact of infertility on marital adjustment, sexual functioning, QoL and the acceptability of various treatment modalities in infertility. Design and Setting : Hospital-based cross-sectional controlled study. Materials and Methods : Data regarding infertility, socio-demographic characteristics and treatment acceptability was obtained via a semi-structured questionnaire. validated, standardized scales were used to measure marital adjustment (abbreviated dyadic adjustment scale), sexual functioning (abbreviated sexual functioning questionnaire) in cases and controls, and quality of life (FertiQol) in cases. Data from 106 women attending tertiary infertility centers who met the definition of primary infertility and 212 controls attending the medical outpatient department in the same centers was obtained. Results : Body mass index and socioeconomic status were significant (P < 0.006 and < 0.0001 respectively) for infertility. Fertility-enhancing regimens and adoption had the highest acceptability with a wide dispersion of range for adoption and least acceptance for sperm, egg, embryo donation and surrogate motherhood. Logistic regression analysis revealed a significant effect size of infertility on marital adjustment (Nagelkerke R 2 0.725, Cohen's D 0.86) and sexual functioning (Nagelkerke R 2 0.73, Cohen's D 0.815). QoL showed a decrease in mean scores on the FertiQol scale similar to normative data. Conclusions : Effective counseling, reassurance and measures to reduce the impact of the condition on marital and sexual life, overall QoL are needed to impart a holistic treatment in infertility.